Peranan Kemerdekaan Terhadap Kesejahteraan Rakyat di Kalimantan Timur - Irwan, Sayid (Universitas 17 Agustus 1945 Samarinda, 2016)
The aim of this research is wiling to know the condition of the welfare of the East Kalimantan citizen. The location of it is in East Kalimantan in 2016.The method of the it is library research.The results are (1).The inflation in July 2016 is 2,08 % (two point eight) procents, (2). The gap of the citizen income is growing well from year to year, (3). To minimize the the gap the Provinsial government as well as the local ones to encourage the distribution of the nine main needs especially to the outskirts, (3). To give the subsidy the remote, boarders and rural as well,(4). The strengthen of the role of the supervisor of regional inflation, (5). To minimize the breaking of the working realtion (6).Strengthening the role of Regional Inflation Control Team, (7). Regarding the issue of unemployment, the government recognizes that many companies mining and plantation work cut ties to their workers, (8). While from January to July 2016, there have been 520 (five hundred eighttwenty) companies that break the 5662 (five thousand six hundred and sixty-two)employees, (9). Provincial Government to seek programs that encourage labor-intensive investments, (10). Empower micro, small, and poverty because the Central Bureau of Statistics in March 2016 illustrates the increase in the number of poor people in East Kalimantan. Researchers gave suggestions as follows: (1). By the age of 71 (seventy-one) years sought the collaboration between the various parties to improve the economy of East Kalimantan; (2). Labor-intensive job creation, (3).Their market operations and market surveillance,(4).Pressing the termination of employment in order to reduce unemployment, (5).Government subsidies provincial and city/county.